Prevalence of Human T- cell Lymphoma/Leukaemia Virus among Sudanese Blood Donors in Wad Medani, Sudan - Saliheen, Sara A; Mustafa, Awad Elseed; Mohammed, Sumia Elhag (مجلة الجزيرة للعلوم الصحية; مجلد 12 عدد 2 (2016), 2016)
Abstract: Background: HTLV type I/II is a blood borne infection that can be transmitted via blood transfusion. Objective : To determine the seroprevalence of human T – lymphotropic virus among blood donors in Wad Medani Central Blood Bank, Sudan. Methods : A total of 540 serum samples were collected from blood donors who visited the Wad Medani Central Blood Bank from January to July 2013. These sera were screened by ELISA for the determination of antibodies to T- Human Cell Lymphotropic Virus type 1/11.  Results : Only one out of 540 (0.2%) samples was found to be positive for HTLV-I/II while 539 (96.4%) samples were negative. Conclusion: The seroprevalence of HTLV-I/II among the blood donors in Wad Medani Central Blood Bank was found to be very low, 0.20%. Therefore, there is no need for routine screening of blood donors for this virus. The introduction of these extra serological tests to the tests that already were carried out may have an extra financial burden, but because of the seriousness of the diseases that were caused by this virus, these tests should be carried out.